EFFECT OF GIVING BLOCK GLIRICIDIA LEAF TO THE OCCURRENCE AND INTENSITY OF ESTRUS IN BALINESE CATTLE WITH ANETSRUS POSTPARTUM - Demetouw, Bobby Edwin; Samsuri,; I Nyoman Sulabda,; I Made Merdana, (Buletin Veteriner Udayana, 2024)
Anestrus is the main cause of prolongation of birth intervals, thus reducing the productivity of beef cattle. This study aims to determine the effect of giving gliricidia leaf block on the emergence and sensitivity of estrus in balinese cattle experiencing postpartum anestrus. This research method is in the form of balinese cattle anestrus postpartum which were selected as many as 6 cattle. The results of this study showed that giving gliricidia leaves for 14 days and estrus checking for 28 days did not produce significant changes in color, swelling, or mucus in the cattle's vulva observed during the observation period P0 to P4. The average temperature of the vulva also did not experience a significant increase from P0 to P4. There were no significant changes in the riding parameters of companions during the same observation period. Giving gliricidia leaf block for 14 days and checking estrus for 28 days did not have a significant effect on the estrus sensitivity of balinese cattle with postpartum anestrus. Further research should be done on giving gliricidia leaves to increase estrus in balinese cattle with postpartum anestrus.